Hymns of the Wabvuwi - Kauffman, Robert A. (International Library of African Music, 1960)
The Wabvuwi, a Methodist laymen’s organisation in Southern Rhodesia, has developed an interesting style of singing that is becoming increasingly popular in the African churches. The songs are based on European hymns, but the style is purely African. The rhythmic vitality and the interweaving of contrapuntal harmonies make this music sufficiently interesting for careful analysis and for observation of an important direction in which some African church music is moving. Wabvuwi (meaning “Fishermen”) originated about 1940 as a result of the influence of a similar group for women, known as the Rukwadzano, organised eight years earlier. Both groups are highly evangelistic and have high standards of ethical behaviour as prerequisites for membership. Candidates serve as novices for two years before becoming full members. During this time they must prove their willingness to leave their jobs at any time they feel led to render some service. They have often been instrumental in recruiting church members and even in starting new churches. They meet together regularly to pray extemporaneously and to give spontaneous expressions of their faith. Frequently they burst into song during these meetings, and it is these songs particularly that have made the Wabvuwi well known in Southern Rhodesia.
Keywords: Hymns; Methodist Church; Ethnomusicology; Choral music; Musicians; Zimbabwe; African Music